Ketone Ester Treatment Improves Cardiac Function and Reduces Pathologic Remodeling in Preclinical Models of Heart Failure. (January 2021) - Yurista, Salva R.; Matsuura, Timothy R.; Silljé, Herman H.W.; Nijholt, Kirsten T.; McDaid, Kendra S.; Shewale, Swapnil V.; Leone, Teresa C.; Newman, John C.; Verdin, Eric; van Veldhuisen, Dirk J.; de Boer, Rudolf A.; Kelly, Daniel P.; et al.
Abstract : Background: Accumulating evidence suggests that the failing heart reprograms fuel metabolism toward increased utilization of ketone bodies and that increasing cardiac ketone delivery ameliorates cardiac dysfunction. As an initial step toward development of ketone therapies, we investigated the effect of chronic oral ketone ester (KE) supplementation as a prevention or treatment strategy in rodent heart failure models. Methods: Two independent rodent heart failure models were used for the studies: transverse aortic constriction/myocardial infarction (MI) in mice and post-MI remodeling in rats. Seventy-five mice underwent a prevention treatment strategy with a KE comprised of hexanoyl-hexyl-3-hydroxybutyrate KE (KE-1) diet, and 77 rats were treated in either a prevention or treatment regimen using a commercially available β-hydroxybutyrate-(R)-1, 3-butanediol monoester (DeltaG; KE-2) diet. Results: The KE-1 diet in mice elevated β-hydroxybutyrate levels during nocturnal feeding, whereas the KE-2 diet in rats induced ketonemia throughout a 24-hour period. The KE-1 diet preventive strategy attenuated development of left ventricular dysfunction and remodeling post-transverse aortic constriction/MI (left ventricular ejection fraction±SD, 36±8 in vehicle versus 45±11 in KE-1; P =0.016). The KE-2 diet therapeutic approach also attenuated left ventricular dysfunction and remodeling post-MI (left ventricular ejection fraction, 41±11 in MI-vehicle versus 61±7 in MI-KE-2; P <0.001). In addition, ventricular weight, cardiomyocyte cross-sectional area, and the expression of ANP (atrial natriuretic peptide) were significantly attenuated in the KE-2–treated MI group. However, treatment with KE-2 did not influence cardiac fibrosis post-MI. The myocardial expression of the ketone transporter and 2 ketolytic enzymes was significantly increased in rats fed KE-2 diet along with normalization of myocardial ATP levels to sham values. Conclusions: Chronic oral supplementation with KE was effective in both prevention and treatment of heart failure in 2 preclinical animal models. In addition, our results indicate that treatment with KE reprogrammed the expression of genes involved in ketone body utilization and normalized myocardial ATP production following MI, consistent with provision of an auxiliary fuel. These findings provide rationale for the assessment of KEs as a treatment for patients with heart failure. Abstract : Supplemental Digital Content is available in the text.